2008
DOI: 10.1002/ajmg.b.30861
|View full text |Cite
|
Sign up to set email alerts
|

Association of the dopamine transporter (SLC6A3/DAT1) gene 9–6 haplotype with adult ADHD

Abstract: ADHD is a neuropsychiatric disorder characterized by chronic hyperactivity, inattention and impulsivity, which affects about 5% of school-age children. ADHD persists into adulthood in at least 15% of cases. It is highly heritable and familial influences seem strongest for ADHD persisting into adulthood. However, most of the genetic research in ADHD has been carried out in children with the disorder. The gene that has received most attention in ADHD genetics is SLC6A3/DAT1 encoding the dopamine transporter. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 24 publications
8
50
0
2
Order By: Relevance
“…In summary, our findings are in accordance with studies favoring the nine-repeat allele as a risk allele for ADHD in adults (van Dyck et al, 2005;Franke et al, 2008Franke et al, , 2010, but not with studies favoring the 10-repeat allele that seems to be the risk allele for ADHD in children (Chen et al, 2003;Cook et al, 1995;Curran et al, 2001). Here the nine-repeat allele was associated with abnormalities in cognitive response control and related cortical activation in ADHD patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In summary, our findings are in accordance with studies favoring the nine-repeat allele as a risk allele for ADHD in adults (van Dyck et al, 2005;Franke et al, 2008Franke et al, , 2010, but not with studies favoring the 10-repeat allele that seems to be the risk allele for ADHD in children (Chen et al, 2003;Cook et al, 1995;Curran et al, 2001). Here the nine-repeat allele was associated with abnormalities in cognitive response control and related cortical activation in ADHD patients.…”
Section: Discussionsupporting
confidence: 89%
“…However, findings are heterogeneous and may depend on the specific statistical analysis method (Todd et al, 2005;Li et al, 2006;Yang et al, 2007;Langley et al, 2005;Cheuk et al, 2006). Furthermore, in adult samples, the nine-repeat allele has been shown to be associated with the disease, suggesting a differential association depending on age, and a role of SLC6A3 in modulating the ADHD phenotype over life time (Franke et al, 2008(Franke et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Barkley et al 9/10 heterozygous repeat in DAT1 gene was different in many respects with 10/10 allele; such as having severe ADHD, more symptoms, many behavioral problems in childhood and adolescence, weaker relationship with parents and even learning problems at school in adolescence (27). In the study by Franke et al a significant association was found between DAT1 gene and ADHD and in this respect, the present study is consistent with the results of other researchers (28).…”
Section: Discussionsupporting
confidence: 82%
“…Recent investigation has also found in adults with ADHD the association replicated in the present study. 2 Research on gene and environment interaction has evidenced that the 6-repeat allele of the 30-bp VNTR polymorphism may moderate the impact of the SLC6A3/DAT1 on ADHD symptoms, suggesting that DAT1 would affect only those individuals exposed to psychosocial adversity. 6 A previous study that investigated the same polymorphism in a Brazilian sample compounded by children with ADHD observed no preferential transmission from parents to probands of any allele at the 3 region of the gene, including the VNTR of intron 8.…”
mentioning
confidence: 99%
“…Among the dopaminergic genes, the one that has received most attention in ADHD genetics is the SLC6A3/DAT1 encoding the dopamine transporter, a transmembrane protein responsible for the presynaptic reuptake of dopamine. 2 The 52.6 kb human SLC6A3 is located on chromosome 5p.15.3. Persistance into adulthood may represent a promising marker for studying the genetic background of ADHD.…”
mentioning
confidence: 99%